Determining factors influencing environmental knowledge and place attachment on urban residents’ environmental responsible behaviour in urban green space of Henan Province, China: The role of situational factors as a moderator - Guo, Xiaohui; Khatibi, Ali; Tham, Jacquline (Edelweiss Applied Science and Technology, 2025)
From the perspective of emotional and rational integration, we analyze the environmental responsibility behaviors of urban residents in urban green spaces, such as parks, squares, and street green spaces, in order to provide a scientific basis for urban green space management. Based on ABC attitude theory, this paper takes urban green spaces in Henan Province, China, as a case study and explores the factors influencing urban residents’ environmentally responsible behaviors by combining relevant literature and integrating green space characteristics. The framework of this study considers environmental knowledge as a cognitive factor and place attachment as an affective factor, while introducing situational factors as moderating variables. Among them, environmental knowledge is divided into two dimensions: subjective knowledge and objective knowledge, and the affective factor of place attachment is included from the perspective of the people-place relationship, which is integrated into the basic model as a mediating variable in order to examine the relationship between place attachment in environmental knowledge and environmentally responsible behavior. Based on 558 valid questionnaires collected in representative cities in Henan Province, this study constructed a model of the mechanisms influencing urban residents’ environmentally responsible behaviors and empirically validated the theoretical model using structural equation modeling. The results show that environmental knowledge under each measurement dimension has a significant positive effect on environmental responsibility behavior and place attachment, with path coefficients of 0.419 and 0.775, respectively; and place attachment (path coefficient 0.469) also has a significant positive effect on environmental responsibility behavior. In addition, place attachment played a significant mediating role between perceived value and environmentally responsible behavior. Therefore, by enhancing the perceived value of green activities for urban residents, their sense of belonging to the local community can be enhanced, thereby stimulating conscious participation in environmental actions.